2016
DOI: 10.1584/jpestics.j16-01
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the mode of action of neurotoxic insecticides

Abstract: Many of the commercially available insecticides target the nervous system of insects, which are important targets of insecticides. We investigated the mechanism of action of the compound acts on voltage-sensitive sodium channel (Vssc) and nicotinic acetylcholine receptor (nAChR), and the associated mechanism of resistance, mainly using an electrophysiological method. The mechanism of resistance to pyrethroids in A. aegypti, that to neonicotinoids in A. gossypii, and the mechanism of action of the natural produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…However, inhibition of AChE leads to accumulation of ACh in the synaptic cleft resulting in impaired neurotransmission thus succumbing mosquito to death 5 . Insecticides belonging to class of organophosphates and carbamates functions by efficiently inhibiting AChE 6 . However, at present, the drawback for many of such insecticides is their indiscriminate rates of application, environmental hazards and evolution of resistance amongst mosquito vectors, thereby paving the way for development of safer, non-toxic and environment friendly alternatives.…”
Section: Revealing the Molecular Interplay Of Curcumin As Culex Pipie...mentioning
confidence: 99%
“…However, inhibition of AChE leads to accumulation of ACh in the synaptic cleft resulting in impaired neurotransmission thus succumbing mosquito to death 5 . Insecticides belonging to class of organophosphates and carbamates functions by efficiently inhibiting AChE 6 . However, at present, the drawback for many of such insecticides is their indiscriminate rates of application, environmental hazards and evolution of resistance amongst mosquito vectors, thereby paving the way for development of safer, non-toxic and environment friendly alternatives.…”
Section: Revealing the Molecular Interplay Of Curcumin As Culex Pipie...mentioning
confidence: 99%
“…Albopictus and other agricultural pests simultaneously [14] . And reports showed that nornicotine‐typed compounds have certain activities for AChE, and this activity may be an important reason for their anti‐insect activity [2a,15] …”
Section: Resultsmentioning
confidence: 99%
“…Insecticides, such as pyrethroids and neonicotinoids, which target the voltage-sensitive sodium channels or nicotinic acetylcholine receptors, respectively, may directly impair neuronal transmission, muscle activation (Hirata, 2016), and therefore locomotor activity (walking, flying). Moreover, some pesticides, like fungicides, may reduce energy production (Degrandi-Hoffman et al, 2015) and therefore affect locomotion, especially flight capacity, as flying is one of the most intense and energy-demanding physiological processes in insects (Dudley, 2000).…”
Section: Locomotionmentioning
confidence: 99%